Republika australijska — zarys problemu - Kandzia, Agnieszka (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Australian Republic — an outline of the problem „Australian Republic” project is current political problem in Australian politics for over two hundred years. It was born, when Australia was a penal colony. It was developed for years, and nowadays it still arouses great emotions. The constitutional referendum, which was held in 1999, has shown that Australians are not ready for a republic and rejection of British monarchy as a head of state. There are still a lot of debates and discussions about this project. Republicans prepare to the next steps and activities. Republican movement has changed for years. This article shows the short history of Australian republicanism, current concepts and the public opinion support. Key words: republic, political problem, constitutional referendum, republican movement